CLINICAL AND NEUROLOGICAL ASPECTS OF FRAILTY SYNDROME - Rakhimbaeva, G.S.; Khodjaeva, M.F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Frailty syndrome is an age–related pathology characterised by a decrease in physical and functional activity, and a lack of adaptive and therapeutic capabilities of the patient. The study of the features of neurological deficits in patients with senile asthenia is an urgent problem of modern medicine. The article describes the principles of the dynamics of subjective and objective neurological symptoms, cognitive indicators in frailty syndrome and treatment of these patients, and prevention and organisation of medical care for this category of persons.